Resolution of non-psychogenic epileptic-like seizures utilizing a vasodilatory and anti-inflammatory dietary intervention - Mamo, John (Nature Publishing Group, 2016)
A young female subject with ineffective pharmacological regulation of chronic vasoconstrictive-induced epilectic-like seizures was effectively treated with a dietary regimen targeted to promote vasodilatation and attenuate vascular inflammation. The intervention consisted of complete cessation of caffeinated beverages, supplementation with L-arginine to promote vasodilatation, consumption of foods rich in phytoestrogens, minimization of foods enriched with saturated fatty acids, supplementation with vitamin D concomitant with increased ingestion of dairy milk and supplementation with aged garlic extract.